Profiling of Catfish Swim Bladder Collagen (Pangasius sp.) Through Enzymatic Proses - Gevbry Ranti Ramadhani Simamora; Wini Trilaksani; Uju Uju (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Swim bladder is a marine byproduct and a potential source of collagen needed by food, cosmetical, biomedical and pharmaceutical industry. This study evaluated the effectiveness of alkaline pretreatment and papain enzyme on the characteristics of collagen from the catfish swim bladders. TThree concentrations of alkaline (0.05; 0.1 and 0.15 M) with were used to pretreat the swim bladders for 2; 4; 6; 8; 10 and 12 hours. The collagen was also treated by papain enzyme with concentrations of 0; 5,000; 10,000; 15,000 and 20,000 U/mg for 24 and 48 hours. The result showed that pretreatment using NaOH 0.05 M for 6 hours effectively reduced the noncollagen protein (p<0.05). Meanwhile, the treatment using papain enzyme with concentration of 5.000 U/mg for 48 hours improved the collagen solubility. The FTIR of collagen showed the existence of a triple helix structure. Meanwhile, the thermal analysis showed collagen gelation transition temperature (Tg) was at 88oC.